Penggunaan Vermikulit Dan Kapur Pada Kuat Tekan Bebas Dan Kuat Geser Tanah Lempung - Saputrah, Yosrin Adi; Sariman, Syahrul; Yusuf, A. Rumpang (Program Studi Teknik Sipil Universitas Bosowa, 2026)
Clay soil is a soil that has a high potential for shrinkage if there is a change in the soil water content system. Expansive soil has a large shrinkage. Stabilization of clay soil is an important step in geotechnical engineering to improve the physical and mechanical properties of the soil, especially in supporting building structures. This study aims to evaluate the effect of adding vermiculite and lime on the unconfined compressive strength (UCS) and shear strength of clay soil. Vermiculite, as a mineral additive material that has high expansion and cation exchange capacity, combined with lime which is chemically able to improve soil stability and strength through pozzolanic reactions. One method of improving expansive clay soil is by adding vermiculite and lime as soil stabilization materials. In this study, shear strength and compressive strength tests will be carried out on soil samples stabilized with vermiculite and lime. This study used 6% vermiculite and variations of lime at 0%, 5%, 10%, 15% which were then tested using the UCS test and direct shear test. The results of the study showed that the highest shear strength, cohesion, and friction angle values were obtained with the addition of 6% vermiculite and 15% lime, namely 0.9247% for shear strength, 0.4392% for cohesion, and 27.57% for friction angle. Similarly, in the compressive strength test, the highest increase occurred with the addition of 6% vermiculite and 15% lime with a stress value of 1.155%.